Visual-based emotion recognition - Lakshmen, C. N. N. (2012)
Emotions play an important role in a human being’s daily life as it provides them with a very powerful and natural tool to communicate their feelings and intensions. Although humans can recognise emotions effortlessly, computers/machines are not able to do it with such accuracy. Automatic emotion recognition by computers/machines still remains as an issue to be solved. Achieving automatic emotion recognition is important for applications such as Human-Computer Interaction (HCI).